Selective progesterone receptor modulators (SPRMs): progesterone receptor action, mode of action on the endometrium and treatment options in gynecological therapies. (1st September 2016) - Wagenfeld, Andrea; Saunders, Philippa T.K.; Whitaker, Lucy; Critchley, Hilary O.D.
ABSTRACT: Introduction : The progesterone receptor plays an essential role in uterine physiology and reproduction. Selective progesterone receptor modulators (SPRMs) have emerged as a valuable treatment option for hormone dependent conditions like uterine fibroids, which have a major impact on women's quality of life. SPRMs offer potential for longer term medical treatment and thereby patients may avoid surgical intervention. Areas covered : The authors have reviewed the functional role of the progesterone receptor and its isoforms and their molecular mechanisms of action via genomic and non-genomic pathways. The current knowledge of the interaction of the PR and different SPRMs tested in clinical trials has been reviewed. The authors focused on pharmacological effects of selected SPRMs on the endometrium, their anti-proliferative action, and their suppression of bleeding. Potential underlying molecular mechanisms and the specific histological changes in the endometrium induced by SPRMs (PAEC;P rogesterone receptor modulatorA ssociatedE ndometrialC hanges) have been discussed. The clinical potential of this compound class including its impact on quality of life has been covered. Expert Opinion : Clinical studies indicate SPRMs hold promise for treatment of benign gynecological complaints (fibroids, heavy menstrual bleeding; HMB). There however remains a knowledge gap concerning mechanism of action.